2003
DOI: 10.1074/jbc.m308231200
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Anionic Micelle-mediated α-Synuclein Fibrillization in Vitro

Abstract: Parkinson's disease is characterized by the aggregation of ␣-synuclein into filamentous forms within affected neurons of the basal ganglia. Fibrillization of purified recombinant ␣-synuclein is inefficient in vitro but can be enhanced by the addition of various agents including glycosaminoglycans and polycations. Here we report that fatty acids and structurally related anionic detergents greatly accelerate fibrillization of recombinant ␣-synuclein at low micromolar concentrations with lag times as short as 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
206
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(221 citation statements)
references
References 77 publications
12
206
1
2
Order By: Relevance
“…Although it was previously known that membranes or detergents can facilitate the aggregation of αS (32,33), and the protein is highly helical when bound to membranes or detergents as a monomer (3,(26)(27)(28)(29)33), it has never previously been shown, to the best of our knowledge, that any helical αS conformations are directly involved in inducing the aggregation of this protein. Ahmad et.…”
Section: Discussionmentioning
confidence: 91%
“…Although it was previously known that membranes or detergents can facilitate the aggregation of αS (32,33), and the protein is highly helical when bound to membranes or detergents as a monomer (3,(26)(27)(28)(29)33), it has never previously been shown, to the best of our knowledge, that any helical αS conformations are directly involved in inducing the aggregation of this protein. Ahmad et.…”
Section: Discussionmentioning
confidence: 91%
“…Besides studying the structural basis for the putative physiological functions of ␣-synuclein, SDSL could also be used to investigate the conformational changes involved in the transition from unfolded or helical synuclein into toxic oligomeric forms (40). In this respect, it is interesting to note that, at least under some conditions, membrane interaction can facilitate the formation of such oligomers (41)(42)(43) and that modulation of the membrane interaction could be responsible for the formation of toxic oligomers in vivo (44,45). Thus, the molecular understanding of the helical, membrane-bound form discussed here might prove to be an important starting point for our understanding of the misfolding that occurs in disease.…”
Section: Discussionmentioning
confidence: 99%
“…Inasmuch as a continuous ␣-helix of 90 or more amino acids would be at least 130 Å long, it would have to almost completely wrap around SDS micelles, but span only Ϸ20% of the small unilamellar vesicle circumference. The curvature strain of SDS micelles might therefore require breakage of the elongated helix near its midpoint (residues [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that the process of nucleation of α-synuclein amyloid fibrils is likely to be heterogeneous and catalyzed by environmental features, such as air-water interfaces (26,27), lipid bilayers (28), SDS micelles and other anionic surfactants (11,29,30), or artificial interfaces such as the coatings of containers or stir bars (31). In addition, mechanical action, such as shaking and stirring, is often used to accelerate the aggregation of α-synuclein (32).…”
Section: Primary Nucleation and Fragmentation Can Be Selectively Enhamentioning
confidence: 99%